DIMENSIONAL PERILAKU KEPEMIMPINAN MELAYANI DALAM MENINGKATKAN KINERJA DI DALAM PERAN, DENGAN KETERLIBATAN KERJA SEBAGAI MEDIASI - Mulyaningrum, Eka; Chrsta, Ussup Riassy; Tunjang, Hansly; Mahrita, Ani (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2023)
The objective of this study is to investigate the behavior of servant leadership (BSL) in enhancing in role performance. The role of work involvement was also examined as a mediator by the researchers. The study employed a survey methodology to collect data from 128 civil servants in Central Kalimantan. Out of the total respondents, 96 individuals willingly and accurately completed the questionnaire. The employed analytical approach utilises the hierarchical component model (HCM) and entails the examination of the second-order model that encompasses a dual-layered structure within the partial least squares structural equation modelling (PLS-SEM) framework to assess the proposed hypotheses. The results indicate that the manifestation of servant leadership behaviour, also known as BSL, has the potential to enhance one's performance within their designated role. Furthermore, the construct of job involvement (JI), assumes a significant function as a mediator in the examined associations. This study aims to investigate the various dimensions of servant leadership behaviour and its impact on role performance within government organisations in Indonesia. Additionally, the study seeks to explore the potential mediating role of work involvement in this relationship.